Influence of heat treatment on tribocorrosion properties of Ni-B composite coatings - M. Khoma; R. Mardarevych; V. Vynar; Сh. Vasyliv; Yu. Kovalchyk (Проблеми трибології, 2022)
Various surface protection technologies, in particular, electrochemical, are used to increase the wear and corrosion resistance of steels and alloys. Composite electrochemical coatings (CEC) technology is more promising than "pure" galvanic coatings. Application of CEC increases the wear, corrosion and fatigue failure resistance of metals. Nickel often is chosen as a CEC matrix because it easily forms uniformly filled defect-free composite structures with many particles of the dispersed phase (DP).